The state of agricultural extension and advisory services provision in Malawi: Insights from household and community surveys - Ragasa, Catherine; Niu, Chiyu (International Food Policy Research Institute, 2017)
This is part of a series of descriptive reports and later in-depth analysis of the survey data. These series are aimed to provide an assessment of the state of agricultural extension and advisory services provision in Malawi in order to inform policy and reform processes and programming by the government and donors. These studies are in response to the re-quest by the Ministry of Agriculture, Irrigation and Water Development (MoAIWD) to look closely at the state of extension services provision with the intent to further strengthen the contribution such services make to food security, economic growth, and achieving sustainable development goals. This report summarizes key findings on the state of agriculture and nutrition extension and advisory services in Malawi based on responses from household and community surveys conducted in Malawi between August and October 2016 that focused on the demand side of agricultural extension service provision and access to those services. Nationally representative samples of 3001 households and 299 communities in all districts of Malawi, except Likoma, were interviewed for the study.